Efeito do laser de baixa potência (660nm) na tendinite induzida por colagenase em tendão calcâneo de ratos - Silva, Romildo Torres da (2013)
Tendinopathy is a common disease with a variety of treatments and therapies. Laser therapy appears as a alternative treatment. We research the effects of the laser irradiation in tendinitis model induced by collagenase injection on Achilles tendon rats, verified its action in important inflammatory markers. Methods: The male rats (Wistar) were used and divided in groups: Saline (C), Tendinitis (NT) and tendinitis treated with Sodium diclofenac (D) or Laser (1J) and (3J). The tendinitis was induced by collagenase (100μg/tendon) on the Achilles tendon which was removed for analyzes. The gene expression for COX-2; TNF-α; il-6 and IL-10 (RT-PCR) was measured. Results and discussion: The Laser therapy (660nm, 100mW, 3J) used in the treatment of the tendinitis induced by collagenase in Achilles tendon in rats, was effective in the reduction of important inflammatory markers, becoming a promising tool for the treatment of tendon diseases.